The role of perceived social support, vocational self-efficacy and vocational outcome expectation on students’ interest in the TVET program - Azeem, Nazia; Omar, Muhd Khaizer; Mat Rashid, Abdullah; Abdullah, Arnida; Zaremohzzabieh, Zeinab (Karadeniz Technical University, 2021)
This study aimed at examining the predictors of students’ interest in the Technical and Vocational Education and Training (TVET) program among secondary school students in Pakistan. The sample of the study consisted of 386 secondary school students randomly drawn from the schools of Pakistan. For data collection, a set of self-reported questionnaire was designed, and multiple linear regression was conducted to evaluate the hypotheses raised for the study. Based on the social cognitive career theory, three variables were assessed. The combination of the research variables significantly contributed 61.2% (R 2 =0.61) to students’ interest in the TVET program. Meanwhile, vocational self-efficacy was found to be the most dominant factor contributing to students’ interest in the TVET program. In the light of these findings, it is suggested for intervention designed to increase secondary school students’ interest to take vocational self-efficacy into consideration. Finally, ideas for future research were discussed.